2019
DOI: 10.1177/0146167219858652
|View full text |Cite
|
Sign up to set email alerts
|

Stepping into Perpetrators’ Shoes: How Ingroup Transgressions and Victimization Shape Support for Retributive Justice through Perspective-Taking With Perpetrators

Abstract: Three experiments (total N = 1,061) examined the morally disengaging function of perspective-taking with ingroup perpetrators in intergroup conflict. In the context of the Iran–U.S. conflict, Americans who strongly identified with their country showed increased perspective-taking with perpetrators, which in turn led to reduced support for retributive justice in response to the perpetration rather than suffering of intergroup violence (Experiment 1; N = 191). Experiment 2 ( N = 294) replicated these findings in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…A large literature examining social identification has consistently shown that individuals are motivated to defend their group to the extent that they identify with it (e.g., (Branscombe, Ellemers, Spears, & Doosje, 1999). Since high identifiers are motivated to uphold a positive ingroup image (Doosje & Branscombe, 2003;Doosje, Branscombe, Spears, & Manstead, 2006), they tend to justify or even deny the wrongfulness of their groups' actions to protect their identity (e.g., Bilali, Tropp, & Dasgupta, 2012;Li, Leidner, & Fernandez-Campos, 2019;Lowery, Knowles, & Unzueta, 2007). Low identifiers, by contrast, tend to be more ingroup critical, experience more group-based guilt, and are therefore more likely to react in a compensatory manner in response to negative portrayals of the ingroup (e.g., Doosje et al, 2006;Klein, Licata, & Pierucci, 2011;Roccas, Klar, & Liviatan, 2006).…”
Section: The Moderating Role Of Ingroup Identificationmentioning
confidence: 99%
“…A large literature examining social identification has consistently shown that individuals are motivated to defend their group to the extent that they identify with it (e.g., (Branscombe, Ellemers, Spears, & Doosje, 1999). Since high identifiers are motivated to uphold a positive ingroup image (Doosje & Branscombe, 2003;Doosje, Branscombe, Spears, & Manstead, 2006), they tend to justify or even deny the wrongfulness of their groups' actions to protect their identity (e.g., Bilali, Tropp, & Dasgupta, 2012;Li, Leidner, & Fernandez-Campos, 2019;Lowery, Knowles, & Unzueta, 2007). Low identifiers, by contrast, tend to be more ingroup critical, experience more group-based guilt, and are therefore more likely to react in a compensatory manner in response to negative portrayals of the ingroup (e.g., Doosje et al, 2006;Klein, Licata, & Pierucci, 2011;Roccas, Klar, & Liviatan, 2006).…”
Section: The Moderating Role Of Ingroup Identificationmentioning
confidence: 99%
“…Just as victim sensitivity might trigger tensions between personal and group-level concerns among strongly identified group members, beneficiary and perpetrator sensitivities might also give rise to psychological conflicts among highly identified group members. For advantaged groups, for example, high levels of group identification are typically associated with in-group-defensive tendencies, such as less acceptance of the negative portrayal of the in-group (Branscombe et al, 1999), less collective guilt and more disengagement from in-group-committed harm (Doosje et al, 1998;Li et al, 2020), and less willingness to repair the harm (Doosje et al, 2006). Such in-group-defensive tendencies are therefore at odds with the predisposition to experiencing guilt and assuming responsibility implied by high levels of perpetrator or beneficiary sensitivity.…”
Section: Potential Specificities Of Beneficiary and Perpetrator Sensitivities At The Group Levelmentioning
confidence: 99%
“…For instance, research on the roles of group identification in intergroup contexts has yielded complex patterns of results. On the one hand, strong group identification can have conflict-enhancing effects (Li et al, 2020;Roccas & Elster, 2012); on the other hand, it can also foster group-based emotions, such as collective guilt or group-based sympathy, that are conducive of intergroup reconciliation (e.g., Branscombe & Miron, 2004;Doosje et al, 1998;Shuman et al, 2018). Taking into account interindividual differences in how intergroup relations are appraised might be one promising approach to understanding these diverging results.…”
Section: Conclusion and Directions For Further Refinements-research Neededmentioning
confidence: 99%
“…Ironically, but consistent with just world beliefs, these greater perceived benefits and moral obligations were less evident when observers focused on the meaning of the past transgression for members of the perpetrator group (or compared to a control group that did not reflect on the meaning of the experience). However, unlike third-party observers, it is possible that when perpetrator group members seek meaning for themselves in the past harm done by their group (i.e., consider what the events imply about their own group’s actions and moral standing), they might attribute greater benefits and obligations to the victim group as a defensive strategy for protecting their own group identity [ 14 ] and reducing the need for retributive justice [ 20 ].…”
Section: Studymentioning
confidence: 99%